Implementation of The Fuzzy Tsukamoto Method In Predicting Corn Harvest Results in The Office Agriculture of North Sumatra Province - Muhammad Azri; Jaya Tata Hardinata; Yuegilion Pranayama Purba (The IJICS (International Journal of Informatics and Computer Science), 2022)
Corn is a food crop that produces carbohydrates. The increasing need for food is in line with the population growth. The need for corn is an aspect that must be met by the Indonesian government in an effort to prosper the community. in order to determine the quality of corn harvests that are good and in accordance with the desired target. Corn productivity at the North Sumatra Provincial Agriculture Office changes every year. This requires predictions to know the future image for the harvest whether it will increase or decrease. Based on the situation in Simalungun district, a system that can predict corn harvest is needed to assist farmers in predicting how much they will harvest. Results of predicting corn harvest. in North Sumatra Province in 2019 the largest was 767304.6 (tons) and the smallest yield was 51 (tons) and the largest land area was 111386(ha) and the smallest was 554(ha). While the largest harvested area in 2019 was 108898 (ha) and the smallest was 9 (ha). For 2020, the harvested area is 106682 (ha) and the land area is 28412.5 (ha), so the prediction results in 2020 are 205148.16 (tons)